Hydramethylnon induces synergistic toxicity of pyrethroid mixtures in human lung epithelial cells - Hye-Jin Jeong; Hye-In Park; Tae-Rim Im; Ju-Hui Im; Seung Min Choi; Chang-Ik Choi; Myungwon Seo; Yong Joo Park (Toxicological Research, 2026)

Polystyrene microplastics induce skeletal muscle atrophy through disruption of anabolic signaling and mitochondrial function - Soo-Young Choi; Jiyoung Yeo; Yu-Jin Heo; Hae-In Lee; Min-Kyung Nam; Seung-Ah Yoo; Mi-Kyung Lee (Toxicology, 2026)

Local and remote drivers of increased variability in extreme wildfire conditions in Southeastern Australia - Kiwook Kim; Myong-In Lee; Seungseok Lee; Nakbin Choi; Fei-Fei Jin; Seung-Ki Min; Jonghun Kam (Agricultural and Forest Meteorology, 2026)

Quantifying the joint effects of soil salinity and fertility on rice growth and yield variability in coastal paddies of southwestern Korea - Seo-Woo Park; Nuri Baek; Se-In Lee; Eun-Seo Shin; Hyun-Jin Park; Han-Yong Kim; Kyo-Suk Lee; Kwang-Seung Lee; Nurgul Kitir Sen; Woo-Jung Choi (Journal of Soils and Sediments, 2026)

Corrigendum to ‘Comparative evaluation of surface-level PM2.5 modeling across Northeast Asia: relevance for regulatory and scientific applications’ [Environ. Pollut. 377 (2025) 126428] - Hyeon-Kook Kim; EunRyoung Kim; Chang-Keun Song; Jae-Ho Choi; Ganghan Kim; Myong-In Lee; Yujin J. Oak; Rokjin J. Park; Ilhan Ryoo; Seung-Muk Yi; Kyung-Mi Lee; Hyeok-Gi Cheo; et al. (Environmental Pollution, 2026)

Substitution of lithogenic with pedogenic soil carbonates in Korean coastal rice paddy under desalinization: Evidences from δ13C - Seo-Woo Park; Nuri Baek; Eun-Seo Shin; Bo-Seong Seo; Se-In Lee; Kwang-Seung Lee; Seok-In Yun; Hyun-Jin Park; Sang-Mo Lee; Woo-Jung Choi (Agriculture, Ecosystems & Environment, 2026)

Preclinical Pharmacokinetics of DM5167, a Novel Selective PARP1 Inhibitor - Jin Woo Kim; Seung-Won Lee; Myung Eun Jung; Ki-Hong Jang; Hae-In Choi; Yoon Ha Lee; Jeongmin Kim; Sunjoo Ahn; Eunhee Kim; Tae-Sung Koo (Pharmaceutical Research, 2025)

Cation adsorption strategy to increase the impregnation limit of thermally conductive alumina filler in adhesives: mass-producible and eco-friendly scheme for direct industrial application - Yechan Chang; Ahyeon Choi; Dong-In Shin; Hye Sun Park; Jisung Lee; Sooyeol Jeong; Ji-In Park; Ji Yong Bae; I Jong Kim; Sung Woo Lee; Jongchan Lee; Sangyul Baik; et al. (Chemical Engineering Journal, 2025)

Baricitinib-loaded separable microneedle array patch (S-MAP) based on hyaluronic acid for alopecia areata therapy - Da In Jeong; Song Yi Lee; Sungyun Kim; Su-Min Jo; HeeSeon Yang; Jieun You; ChaeRim Hwang; Ji Won Huh; Yeoung Eun Choi; Wonjun Jo; In-Jeong Choi; Hae-Jin Hu; et al. (Carbohydrate Polymers, 2025)

Comparative evaluation of surface-level PM2.5 modeling across Northeast Asia: relevance for regulatory and scientific applications - Hyeon-Kook Kim; EunRyoung Kim; Chang-Keun Song; Jae-Ho Choi; Ganghan Kim; Myong-In Lee; Yujin J. Oak; Rokjin J. Park; Ilhan Ryoo; Seung-Muk Yi; Kyung-Mi Lee; Hyeok-Gi Cheo; et al. (Environmental Pollution, 2025)

Modulating energy band structure of CsPbBr3@TiO2 composites for enhanced photocatalytic and anti-superbacterial performance - Chang-Yeon Kim; Min-Gi Jeon; Artavazd Kirakosyan; Da-Hye Kim; Hea-Jong Chung; Ji-Hyun Lee; Ha-Rim An; Byoungchul Son; Seung Jo Yoo; Sang-Gil Lee; Ji-In Park; Soo Hyeon Kim; et al. (Journal of Water Process Engineering, 2025)

Development of a deep neural network model based on high throughput screening data for predicting synergistic estrogenic activity of binary mixtures for consumer products - Jongwoon Kim; Seung-Jin Lee; Daeyoung Jung; Hyun Young Kim; Jung-In Lee; Myungwon Seo; Sunmi Kim; Jiwon Choi; Wook-Joon Yu; Heeyeong Cho (Journal of Hazardous Materials, 2025)

Thermal maturity and colors of Cretaceous East Asian fossil eggs - Seung Choi; Shukang Zhang; Noe-Heon Kim; Jin Jung Kweon; Kohei Tanaka; Katsuhiro Kubota; Yuong-Nam Lee; Junfang Xie; In Sung Paik; Sung Keun Lee (Sedimentary Geology, 2025)

Signal-off colorimetric and signal-on fluorometric dual-mode aptasensor for ultrasensitive detection of Salmonella Typhimurium using graphitic carbon nitride - Thinh Viet Dang; In Seung Jang; Quynh Huong Nguyen; Hyeun Seok Choi; Byung Jo Yu; Moon Il Kim (Food Chemistry, 2025)

Transparent and visible light-activated antimicrobial air filters from electrospun crystal violet-embedded polyacrylonitrile nanofibers - Seung Yeon Lee; Jae Hak Shin; In Ho Kim; Dong Yun Choi; Dong Uk Lee; Gi Byoung Hwang; Bangwoo Han; Sang Bok Kim; Dong-Keun Song; Inyong Park; Jae Hee Jung (Environmental Research, 2025)

PM exposure during pregnancy affects childhood asthma via placental epigenetic changes: Neuronal differentiation and proliferation and Notch signaling pathways - Hyo-Bin Kim; Si Hyeon Lee; Dae Yeol Yang; Seung-Hwa Lee; Jeong-Hyun Kim; Hwan-Cheol Kim; Kil Yong Choi; So-Yeon Lee; Song-I Yang; Dong In Suh; Youn Ho Shin; Kyung Won Kim; et al. (Environmental Pollution, 2025)

Investigating uncertainties in air quality models used in GMAP/SIJAQ 2021 field campaign: General performance of different models and ensemble results - Yesol Cha; Jong-Jae Lee; Chul Han Song; Soontae Kim; Rokjin J. Park; Myong-In Lee; Jung-Hun Woo; Jae-Ho Choi; Kangho Bae; Jinhyeok Yu; Eunhye Kim; Hyeonmin Kim; et al. (Atmospheric Environment, 2025)

Insights and machine learning predictions of harmful algal bloom in the East China Sea and Yellow Sea - Jiyi Jang; Sang-Soo Baek; Daehyun Kang; Yongeun Park; Mayzonee Ligaray; Seung Ho Baek; Jin Yong Choi; Bum Soo Park; Myong-In Lee; Kyung Hwa Cho (Journal of Cleaner Production, 2024)

Two-in-one strategy: Discretely functionalized electrolyte additive for stable lithium metal batteries coupled with Ni-rich cathode - Yong Min Kim; Jeong In Choi; Bo Keun Park; Ji Woo Han; Jong-Won Lee; Hyun-seung Kim; Ki Jae Kim (Chemical Engineering Journal, 2024)

Preparation of activated carbon from ginkgo leaves by steam activation for adsorption application with isotherm and kinetics - In-Jun Hwang; Thuan Anh Vo; Suk Soon Choi; Jinsoo Kim; Hyun Tae Hwang; Seung-Soo Kim (Biomass and Bioenergy, 2024)

Anti-inflammatory and relaxation effects of Ulmus pumilla L. on EGF-inflamed bronchial epithelial and asthmatic bronchial smooth muscle cells - In-Seung Lee; Yeonjung Choi; Wona Jee; Jihyuk Park; Hyungsuk Kim; Kwanil Kim; Hee-Jae Jung; Hyeung-Jin Jang (Molecular & Cellular Toxicology, 2024)

First report of tomato spotted wilt virus infecting lobelia in South Korea - In-Sook Cho; Bong-Nam Chung; Seung-Kook Choi; Sena Choi; John Hammond; Hyoun-Sub Lim (Journal of Plant Pathology, 2023)

Antiviral activity of canine interferon lambda 3 expressed using a recombinant adenovirus against canine coronavirus, canine parvovirus, and canine distemper virus - Dong-Hwi Kim; Sang-Hoon Han; Hyeon-Jeong Go; Da-Yoon Kim; Jae-Hyeong Kim; Joong-Bok Lee; Seung-Yong Park; Chang-Seon Song; Sang-Won Lee; In-Soo Choi (Veterinary Research Communications, 2022)

Geochemical signatures of organic matter associated with gas generation in the Pohang Basin, South Korea - Dong-Hun Lee; Seung-Hee Kim; Jiyoung Choi; Nyeon-Keon Kang; In Gul Hwang; Kyung-Hoon Shin (Geosciences Journal, 2022)

PKC-β modulates Ca2+ mobilization through Stim1 phosphorylation - Hye-Jin Song; In-Sook Jeon; Seung Ryul Kim; Kwan Sik Park; Jae-Won Soh; Kwang Youl Lee; Jae-Cheon Shin; Hak-Kyo Lee; Joong-Kook Choi (Genes & Genomics, 2022)
Background Calcium ions play a pivotal role in cell proliferation, differentiation, and migration. Under basal conditions, the calcium level is tightly regulated; however, cellular activation by growth factors increase the ion level through calcium pumps in the plasma membrane and endoplasmic reticulum for calcium signaling. Orai1 is a major calcium channel in the cell membrane of non-excitable cells, and its activity depends on the stromal interaction molecule 1 (Stim1). Several groups reported that the store-operated calcium entry (SOCE) can be modulated through phosphorylation of Stim1 by protein kinases such as extracellular signal-regulated kinase (ERK), protein kinase A (PKA), and p21-activated kinase (PAK). PKC is a protein kinase that is activated by calcium and diacylglycerol (DAG), but it remains unclear what role activated PKC plays in controlling the intracellular calcium pool. Objectives Here, we investigated whether PKC-β controls intracellular calcium dynamics through Stim1. Methods Several biochemical methods such as immune-precipitation, site directed mutagenesis, in vitro kinase assay were employed to investigate PKC interaction with and phosphorylation of Stim1. Intracellular calcium mobilization, via Stim1 mediated SOCE channel, were studied using in the presence of PKC activator or inhibitor under a confocal microscope. Results Our data demonstrate that PKC interacts with and phosphorylates Stim1 in vitro. phosphorylation of Stim1 at its C-terminal end appears to be important in the regulation of SOCE activity in HEK293 and HeLa cells. Additionally, transient intracellular calcium mobilization assays demonstrate that the SOCE activity was inhibited by PKC activators or activated by PKC inhibitors. Conclusion In sum, our data suggest a repressive role of PKC in regulating calcium entry through SOCE.

Galuteolin, identified in the extract of thymus quinquecostatus flowers, is involved in inhibiting melanin biosynthesis in B16/F10 melanoma cells - Mi-Hee Kim; Bora Kwon; Kwang-Sang Kim; Min-Sook Kim; Min-Ji Kim; Hwa-Jin Kim; Da-In Choi; Miyeon Park; Moosung Kim; Min-Kyu Shin; Seung-Il Jeong; Kang-Yeol Yu; et al. (Natural Product Research, 2021)

The optimal standard protocols for whole-genome sequencing of antibiotic-resistant pathogenic bacteria using third-generation sequencing platforms - Tae-Min La; Ji-hoon Kim; Taesoo Kim; Hong-Jae Lee; Yoonsuk Lee; Hyunjin Shin; Yongjun Song; Gyuhee Ahn; Won Hur; Joong-Bok Lee; Seung-Yong Park; In-Soo Choi; et al. (Molecular & Cellular Toxicology, 2021)

Mesenchymal Stem Cells Derived from Wharton’s Jelly Can Differentiate into Schwann Cell-Like Cells and Promote Peripheral Nerve Regeneration in Acellular Nerve Grafts - Soon Jin Choi; Suk Young Park; Young Ho Shin; Seung-Ho Heo; Kang-Hyun Kim; Hyo In Lee; Jae Kwang Kim (Tissue Engineering and Regenerative Medicine, 2021)

Resolvin D3 Promotes Inflammatory Resolution, Neuroprotection, and Functional Recovery After Spinal Cord Injury - Juri Kim; Hari Prasad Joshi; Seung Hun Sheen; Kyoung-Tae Kim; Jae Won Kyung; Hyemin Choi; Ye Won Kim; Su Yeon Kwon; Eun Ji Roh; Un Yong Choi; Seil Sohn; Yong Ho Kim; et al. (Molecular Neurobiology, 2021)

Spatio-temporal patterns of the minimum rest time for outdoor workers exposed to summer heat stress in South Korea - Seung-Wook Lee; In-Gyum Kim; Hye-Min Kim; Dae-Geun Lee; Hee-Choon Lee; Gwangyong Choi (International Journal of Biometeorology, 2020)

Biomass, chemical composition, and microbial decomposability of rice root and straw produced under co-elevated CO2 and temperature - Hyun-Jin Park; Sang-Sun Lim; Jin-Hyeob Kwak; Kwang-Seung Lee; Hye In Yang; Han-Yong Kim; Sang-Mo Lee; Woo-Jung Choi (Biology and Fertility of Soils, 2020)

Anti-inflammatory effect of Rosa laevigata extract on in vitro and in vivo model of allergic asthma via the suppression of IgE and related cytokines - Seung-Hyeon Lee; Seung-Han Choi; In-Seung Lee; Yumi Kim; Eun-Jin An; Hyeung-Jin Jang (Molecular & Cellular Toxicology, 2020)

The medicinal mushroom Auricularia auricula - judae (Bull.) extract has antioxidant activity and promotes procollagen biosynthesis in HaCaT cells - Young-Ji Choi; In-Sun Park; Mi-Hee Kim; Bora Kwon; Young-Moo Choo; Seung-Il Jeong; Kang-Yeol Yu; Chung Hyeon Choe; Jiyoung Kim (Natural Product Research, 2019)

TRPV4-Mediated Anti-nociceptive Effect of Suberanilohydroxamic Acid on Mechanical Pain - Geunyeol Choi; Tae-Jin Yang; Sungjae Yoo; Seung-In Choi; Ji Yeon Lim; Pyung Sun Cho; Sun Wook Hwang (Molecular Neurobiology, 2019)

Association of glutathione S-transferase M1 and T1 null/present polymorphism with physical performance in the Korean population - In Wook Hwang; Kicheol Kim; Bit Na Kwon; Hyung Jun Kim; Seung Hun Han; Noo Ri Lee; Eun Ji Choi; Hyun Ik Cho; Han Jun Jin (Genes & Genomics, 2019)

Evidence of hepatitis E virus infection in specific pathogen-free rabbits in Korea - Sang-Hoon Han; Byung-Joo Park; Hee-Seop Ahn; Yong-Hyun Kim; Hyeon-Jeong Go; Dong-Hwi Kim; Joong-Bok Lee; Seung-Yong Park; Chang-Seon Song; Sang-Won Lee; In-Soo Choi (Virus Genes, 2018)

Elevated CO2 concentration affected pine and oak litter chemistry and the respiration and microbial biomass of soils amended with these litters - Hyun-Jin Park; Sang-Sun Lim; Jin-Hyeob Kwak; Hye-In Yang; Kwang-Seung Lee; Young-Han Lee; Han-Yong Kim; Woo-Jung Choi (Biology and Fertility of Soils, 2018)

Combined Poly(Lactide-Co-Glycolide) Microspheres Containing Diphtheria Toxoid for a Single-shot Immunization - Hye Seung Woo; Sung Rae Kim; Mikyeong Yoon; Eun Seok Lee; In Ho Chang; Young Mi Whang; Do Ik Lee; Myung Joo Kang; Young Wook Choi (AAPS PharmSciTech, 2018)

Resistance exercise improves cardiac function and mitochondrial efficiency in diabetic rat hearts - Tae Hee Ko; Jubert C. Marquez; Hyoung Kyu Kim; Seung Hun Jeong; SungRyul Lee; Jae Boum Youm; In Sung Song; Dae Yun Seo; Hye Jin Kim; Du Nam Won; Kyoung Im Cho; Mun Gi Choi; et al. (Pflügers Archiv - European Journal of Physiology, 2018)

Endogenous TRPV4 Expression of a Hybrid Neuronal Cell Line N18D3 and Its Utilization to Find a Novel Synthetic Ligand - Sungjae Yoo; Seung-In Choi; Seul Lee; Jiho Song; Chungmi Yang; Sangsu Bang; Seung Up Kim; Kyung Hoon Min; Sun Wook Hwang (Journal of Molecular Neuroscience, 2017)

Clozapine Improves Memory Impairment and Reduces Aβ Level in the Tg-APPswe/PS1dE9 Mouse Model of Alzheimer’s Disease - Yura Choi; Ha Jin Jeong; Quan Feng Liu; Seung Tack Oh; Byung-Soo Koo; Yeni Kim; In-Won Chung; Yong Sik Kim; Songhee Jeon (Molecular Neurobiology, 2017)

Genetic analysis of COL11A2 in Korean patients with autosomal dominant non-syndromic hearing loss - Sang-Joo Kim; Hong-Joon Park; Borum Sagong; Seung-Hyun Bae; Se-Kyung Oh; Jeong-In Baek; Jae Young Choi; Kyu-Yup Lee; Un-Kyung Kim (Genes & Genomics, 2016)

Whole-transcriptome analysis of mouse adipose tissue in response to short-term caloric restriction - Seung-Soo Kim; Kyung-Mi Choi; Soyoung Kim; Taesun Park; In-Cheol Cho; Jae-Won Lee; Cheol-Koo Lee (Molecular Genetics and Genomics, 2016)

Bladder reconstruction using stem cells seeded on multilayered scaffolds in a mucosa preserving partial cystectomy model - Kshitiz Raj Shrestha; Yong Hyun Park; Yong Sun Choi; In Gul Kim; Shuyu Piao; Ae Ryang Jung; Seung Hwan Jeon; Se Heang Oh; Jin Ho Lee; Ji Youl Lee (Tissue Engineering and Regenerative Medicine, 2015)

Factors Influencing the Spatial Variation of Microplastics on High-Tidal Coastal Beaches in Korea - In-Sung Kim; Doo-Hyeon Chae; Seung-Kyu Kim; SooBong Choi; Seung-Bum Woo (Archives of Environmental Contamination and Toxicology, 2015)

Erratum to: Changes in weather and climate extremes over Korea and possible causes: A review - Seung-Ki Min; Seok-Woo Son; Kyong-Hwan Seo; Jong-Seong Kug; Soon-Il An; Yong-Sang Choi; Jee-Hoon Jeong; Baek-Min Kim; Ji-Won Kim; Yeon-Hee Kim; June-Yi Lee; Myong-In Lee (Asia-Pacific Journal of Atmospheric Sciences, 2015)

Predisposing roles of paraoxonase-1 genetic variants in Korean ischemic stroke patients - Yunkyung Cho; Jung Oh Kim; Young Joo Jeon; Gun Ho Choi; Jee Soo Shin; Sung Hwan Cho; Seung Hun Oh; In Bo Han; Byoung Soo Shin; Ok Joon Kim; Nam Keun Kim (Genes & Genomics, 2015)

Coix seed extract attenuates the high-fat induced mouse obesity via PPARγ and C/EBPα a downregulation - Eun-Kyeong Choi; Yu Jeong Cho; Hea Jung Yang; Ki-Suk Kim; In-Seung Lee; Jong-Chan Jang; Kang-Hoon Kim; Ji Hyun Bang; Yumi Kim; Se Hoon Kim; Young-Hwan Cho; Na Young Yoon; et al. (Molecular & Cellular Toxicology, 2015)

Protective effect of a novel herbmedicine, Hepad, on apoptosis of SH-SY5Y cells and a rat model of Parkinson’s disease - Seung Yeop Baek; Na Rae Lee; Da Hye Kim; Ayoung Gu; Seong Yeol Kim; Dae-Yong Song; Dong-Hee Kim; Hak Joo Choi; Byung-Jun Park; In Sik Kim (Molecular & Cellular Toxicology, 2015)

Analysis of cytokine production in a newly developed canine tracheal epithelial cell line infected with H3N2 canine influenza virus - Woo-Jung Park; Byung-Joo Park; Young-Jo Song; Dong-Hun Lee; Seong-Su Yuk; Joong-Bok Lee; Seung-Yong Park; Chang-Seon Song; Sang-Won Lee; In-Soo Choi (Archives of Virology, 2015)

Changes in weather and climate extremes over Korea and possible causes: A review - Seung-Ki Min; Seok-Woo Son; Kyong-Hwan Seo; Jong-Seong Kug; Soon-Il An; Yong-Sang Choi; Jee-Hoon Jeong; Baek-Min Kim; Ji-Won Kim; Yeon-Hee Kim; June-Yi Lee; Myong-In Lee (Asia-Pacific Journal of Atmospheric Sciences, 2015)

Osteogenic activity of chitosan-based hybrid scaffold prepared by polyelectrolyte complex formation with alginate - Seung Hwan Lee; Ho Yun Chung; Hong-In Shin; Dong-Joon Park; Jin Hyun Choi (Tissue Engineering and Regenerative Medicine, 2014)

Deduced sequences of the membrane fusion and attachment proteins of canine distemper viruses isolated from dogs and wild animals in Korea - Chae-Wun Bae; Joong-Bok Lee; Seung-Yong Park; Chang-Seon Song; Nak-Hyung Lee; Kun-Ho Seo; Young-Sun Kang; Choi-Kyu Park; In-Soo Choi (Virus Genes, 2013)

Immune responses in mice vaccinated with virus-like particles composed of the GP5 and M proteins of porcine reproductive and respiratory syndrome virus - Hae-Mi Nam; Kyung-Sil Chae; Young-Jo Song; Nak-Hyung Lee; Joong-Bok Lee; Seung-Yong Park; Chang-Seon Song; Kun-Ho Seo; Sang-Moo Kang; Min-Chul Kim; In-Soo Choi (Archives of Virology, 2013)

Effects of elevated carbon dioxide and temperature on photosynthesis and fruit characteristics of ‘Niitaka’ pear (Pyrus pyrifolia Nakai) - Jeom-Haw Han; Jung Gun Cho; In-Chang Son; Seung Heui Kim; In-Bog Lee; In Myung Choi; Daeil Kim (Horticulture, Environment, and Biotechnology, 2012)

Serum Selenium Levels in Korean Hepatoma Patients - In-Wook Kim; Su-Mi Bae; Yong-Wan Kim; Hai-Bo Liu; Si Hyun Bae; Jong Young Choi; Seung Kew Yoon; Pankaj Kumar Chaturvedi; Gantumur Battogtokh; Woong Shick Ahn (Biological Trace Element Research, 2012)

Capsaicin-induced apoptosis in the human glioblastoma U87MG cells via p-38 MAPK and Bcl-2/Bax signaling pathway - Jin Ho Jeon; Yoon Ji Choi; In Ho Han; Byung Kwan Choi; Seung Heon Cha; Won Ho Cho (Molecular & Cellular Toxicology, 2012)

Identification of genetic diversity of porcine Norovirus and Sapovirus in Korea - Young-Jo Song; Je-Nam Yu; Hae-Mi Nam; Hyoung-Rok Bak; Joong-Bok Lee; Seung-Yong Park; Chang-Seon Song; Kun-Ho Seo; In-Soo Choi (Virus Genes, 2011)

Anti-angiogenic effects of the water extract of HangAmDan (WEHAD), a Korean traditional medicine - Ji-Young Bang; Kyung-Soon Kim; Eung-Yoon Kim; Hwa-Seung Yoo; Yeon-Weol Lee; Chong-Kwan Cho; YoungJin Choi; Hyun-Ja Jeong; In-Cheol Kang (Science China Life Sciences, 2011)

Ailanthus altissima swingle has anti-anaphylactic effect and inhibits inflammatory cytokine expression via suppression of nuclear factor-kappaB activation - Tae-Hee Kang; In-Young Choi; Su-Jin Kim; Phil-Dong Moon; Jae-Uk Seo; Jae-Joong Kim; Nyeon-Hyung An; Sung-Hoon Kim; Min-Ho Kim; Jae-Young Um; Seung-Heon Hong; Hyung-Min Kim; et al. (In Vitro Cellular & Developmental Biology - Animal, 2010)

Analysis of the helicase gene of Korean swine hepatitis E virus isolates and trends in viral infection - Won-Jung Lee; Mi Lan Kang; Seung-Bin Cha; Bong-Kyun Park; In-Soo Choi; Han Sang Yoo (Archives of Virology, 2009)

AlLTPs from Allium species represent a novel class of lipid transfer proteins that are localized in endomembrane compartments - Seung-In Yi; Mee-Yeon Park; Ju-Kon Kim; Yang Do Choi (Plant Biotechnology Reports, 2009)

Green tea seed oil reduces weight gain in C57BL/6J mice and influences adipocyte differentiation by suppressing peroxisome proliferator-activated receptor-γ - Na-Hyung Kim; Sun-Kyung Choi; Su-Jin Kim; Phil-Dong Moon; Hun-Sun Lim; In-Young Choi; Ho-Jeong Na; Hyo-Jin An; Noh-Yil Myung; Hyun-Ja Jeong; Jae-Young Um; Seung-Heon Hong; et al. (Pflügers Archiv - European Journal of Physiology, 2008)

Hesperidin inhibits expression of hypoxia inducible factor-1 alpha and inflammatory cytokine production from mast cells - In-Young Choi; Su-Jin Kim; Hyun-Ja Jeong; Seong-Heak Park; Yong-Sun Song; Ji-Hyun Lee; Tae-Hee Kang; Jin-Han Park; Gab-Soo Hwang; Eon-Jeong Lee; Seung-Heon Hong; Hyung-Min Kim; et al. (Molecular and Cellular Biochemistry, 2007)

Observations of Forsythia koreana methanol extract on mast cell-mediated allergic reactions in experimental models - In-Young Choi; Phil-Dong Moon; Hyun-Na Koo; Noh-Yil Myung; Su-Jin Kim; Ji-Hyun Lee; Se-Hee Han; Goo Moon; Sung-Yum Seo; Hyun-Jea Sung; Rae-Kil Park; Hyun-Ja Jeong; et al. (In Vitro Cellular & Developmental Biology - Animal, 2007)

Isolation and characterization of a novel rice Ca2 +-regulated protein kinase gene involved in responses to diverse signals including cold, light, cytokinins, sugars and salts - Kyung-Nam Kim; Jung-Sook Lee; Hee Han; Seung Ah Choi; Seung Joo Go; In Sun Yoon (Plant Molecular Biology, 2003)

Movement history of the Andong Fault System: Geometric and tectonic approaches - Pom-yong Choi; Seung Ryeol Lee; Hyen -Il Choi; Jae-ha Hwang; Seok-ki Kwon; In-sae Ko; Gi-o An (Geosciences Journal, 2002)

Intermittent maltose feeding enhances paclitaxel production in suspension culture of Taxus chinensis cells - Hyung-Kyoon Choi; Sang-Ic Kim; Joo-Sun Son; Seung-Suh Hong; Hyun-Soo Lee; In-Sik Chung; Hyong-Joo Lee (Biotechnology Letters, 2000)

Fractional precipitation for paclitaxel pre-purification from plant cell cultures of Taxus chinensis - Jin-Hyun Kim; In-Seon Kang; Hyung-Kyoon Choi; Seung-Suh Hong; Hyun-Soo Lee (Biotechnology Letters, 2000)

Production of biologically active human granulocyte colony stimulating factor in the milk of transgenic goat - Jung Ho Ko; Chul-Sang Lee; Kui Hyun Kim; Myung-Geol Pang; Ja Shin Koo; Nanzhu Fang; Deog-Bon Koo; Keon Bong Oh; Woo-Sik Youn; Guo Dong Zheng; Jung Sun Park; Sun Jung Kim; et al. (Transgenic Research, 2000)

A ncovel angiogenic factor derived from Aloe vera gel: β-sitosterol, a plant sterol - Eun-Joung Moon; You Mie Lee; Ok-Hee Lee; Myoung-Jin Lee; Seung-Ki Lee; Myung-Hee Chung; Young-In Park; Chung-Ki Sung; Jae-Soo Choi; Kyu-Won Kim (Angiogenesis, 1999)